El personaje de la prostituta en la narrativa española y polaca de/sobre la Transición. Un día volveré de Juan Marsé y Niskie Łąki de Piotr Siemion - Kłosińska-Nachin, Agnieszka (Zagadnienia Rodzajów Literackich, 2019)
The figure of the prostitute occupies a privileged position in contemporary Spanish and Polish literature. Departing from the comparative perspective, especially employing the category of world literature according to David Damrosch, the paper aims to explain the relation between the presence of the prostitute as a character in the literary representation of the transition to democracy. To achieve this, the author conducts an analysis of two novels: Un día volveré by Juan Marsé published in 1982 and Niskie Łąki by Piotr Siemion from 1999. In both texts, the analyzed female characters refer to the disillusionment with the moment of the transition to democracy.